Genetic diversity and indirect selection of fine cacao (Theobroma cacao) based on bean color - LUKITA DEVY; INDAH ANITA-SARI; AGUNG WAHYU SUSILO; ADE WACHJAR; SOBIR SOBIR (Biodiversitas Journal of Biological Diversity, 2018)
Devy L, Anita-Sari I, Susilo AW, Wachjar A, Sobir. 2018. Genetic diversity and indirect selection of fine cacao (Theobroma cacao) based on bean color. Biodiversitas 19: 2385-2392. Specialty fine cacaos performed higher price than the bulk thereby the breeding of fine cacao clones become essential. However as perennial tree, cacao clones will be delivered in 15-20 years. Therefore, early detection marker and genetic diversity information will support the fine cacao breeding program. This study aimed to determine genetic parameters and early selection marker of leave flush trait to differentiate fine and bulk cacaos based on white bean percentage/pod (WBP). The research was conducted on 4 fine and 4 bulk cacao clones in two seasons with different rainfall intensities. Observations performed on WBP, flush color (L*, a*, b*, C*, Ho), anthocyanin content (A), SPAD value (S), A/S and S/A. Analysis of variance and T-test result showed that b* and C* were able to differentiate fine from bulk cacaos and stable in two seasons. Almost all traits showed narrow genetic variability except WBP. However, three of them showed high heritability. Traits correlated with WBP were L*, a*, b*, C* and anthocyanin content. However, the trait with high heritability, stable in two seasons, performed differently in two cacao types based on T-test and showing high direct correlation with WBP was only b* (yellow color). Fine cacao showed higher b* than the bulk. Therefore b* of the flush could be considered as a selection marker of fine cacao.